Movement patterns and genetic stock delineation of an endemic South African sparid, the Poenskop, Cymatoceps nasutus (Castelnau, 1861),Movement patterns and genetic stock delineation of an endemic South African sparid, the Poenskop, Cymatoceps nastus (Castelnau, 1861) - Murray, Taryn Sara (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2013)
Poenskop Cymatoceps nasutus (Pisces: Sparidae), an endemic South African sparid, is an important angling species being predominantly targeted by the recreational shore and skiboat sector. This species is slow-growing, long-lived, late-maturing and sex-changing, making poenskop acutely sensitive to over-exploitation. Despite interventions, such as the imposition of size and bag limits (currently 50 cm TL and one per licensed fisher per day) by authorities, catch-per-unit-effort trends reflect a severe and consistent stock decline over the last two decades. Poenskop has been identified as a priority species for research and conservation. Although the biology and population dynamics of this species have been well-documented, little is known about the movement behaviour of poenskop. Furthermore, there is a complete lack of information on its genetic stock structure. This thesis aimed to address the current knowledge gaps concerning movement behaviour and genetic stock structure of poenskop, making use of a range of methods and drawing on available information, including available fishery records as well as published and unpublished survey and research data, and data from long-term monitoring programmes. Analysis of available catch data (published and unpublished) revealed a decline in the number of poenskop caught as well as size of fish taken over the last two decades, ultimately reflecting the collapse of the stock (estimated to be at 20% of their pristine level). Improved catch-per-unit-effort data from the Tsitsikamma National Park Marine Protected Area (MPA), and larger poenskop being caught in the no-take areas than adjacent exploited areas of the Pondoland MPA confirmed that MPAs can be effective for the protection and management of poenskop. The current MPA network in South Africa is already wellestablished, and encompasses considerable reef areas, being preferable for poenskop habitation. Conventional dart tagging and recapture information from three ongoing, long-term fishtagging projects, conducted throughout the poenskop's distribution, indicated high levels of residency at all life-history stages. Coastal region, seasonality and time at recapture did not appear to have a significant effect on the level of movement or distance moved. However, on examining the relationship among coastal movements and fish size and ages, larger and older fish (adults) moved greater distances, with juveniles and sub-adults showing high degrees of residency. An estimation of home-range size indicated smaller poenskop to hold smaller home-ranges, while larger poenskop hold larger home-ranges. Large easterly displacements of a number of adult poenskop is in accordance with previous findings that this species may undertake a unidirectional migration up the coastline of South Africa where they possibly settle in Transkei waters for the remainder of their lives. This high level of residency makes poenskop vulnerable to localised depletion, although they can be effectively protected by suitable MPAs. Despite considerable tagging effort along the South African coastline (2 704 poenskop tagged with 189 recaptures, between 1984 and 2010), there remains limited information on the connectivity of different regions along the South African coastline. This was addressed using mitochondrial DNA sequencing. The mitochondrial DNA control region was used due to its high substitution rate, haploid nature, maternal inheritance and absence of recombination. The mtDNA sequencing showed no evidence of major geographic barriers to gene flow in this species. Samples collected throughout the core distribution of poenskop showed high genetic diversity (h = 0.88, Ï€ = 0.01), low genetic differentiation among regions, no spatial structure (É¸ST = 0.012, p = 0.208) and no evidence of isolation by distance. The collapsed stock status of poenskop as well as the fact that it is being actively targeted by recreational and commercial fishers suggests that this species requires improved management, with consideration given to its life-history style, residency and poor conservation status. Management recommendations for poenskop, combined with increasing South Africa's existing MPA network, include the possibility of setting up a closed season (during known spawning periods) as well as the decommercialisation of this species. The techniques used and developed in this study can also be adopted for other overexploited linefish species.
Keywords: Fish stock assessment -- South Africa; Sparidae -- South Africa; Fishes -- Reproduction -- South Africa; Fishing -- South Africa; Fish populations -- South Africa; Fishes -- Behavior -- South Africa; Marine fishes -- South Africa